Fabrication and simulation of organic transistors and functional circuits - Taylor, D; Patchett, E; Williams, A; Ding, Z; Assender, H; Morrison, J; Yeates, S (Elsevier, 2015)
We report the development of a vacuum-evaporation route for the roll-to-roll fabrication of functioning organic circuits. A number of key findings and observations are highlighted which influenced the eventual fabrication protocol adopted. Initially, the role of interface roughness in determining carrier mobility in thin film transistors (TFTs) is investigated. Then it is shown that device yield is higher in devices fabricated on a flash-evaporated-plasma-polymerised tri(propyleneglycol) diacrylate (TPGDA) gate dielectric than for TFTs based on a spin-coated polystyrene (PS) dielectric. However, a degradation in mobility is observed which is attributed to the highly polar TPGDA surface. It is shown that high mobility and excellent stability are restored when the surface of TPGDA was buffered with a thin, spin-coated PS film. The resulting baseline process allowed arrays of functional circuits such as ring oscillators, NOR/NAND logic gates and S-R latches to be fabricated with high yield and their performance to be simulated